First palynologic record of the Cretaceous La Yesera Formation (Salta Group), northwestern Argentina - Narvaez, Paula Liliana (2014)
Thirty-four taxa were documented from six palynologically productive samples of the La Yesera Formation (Brealito and Don Bartolo Members) in the Pucará locality (Salta Province, northwestern Argentina). In the Brealito Member, aquatic species (mainly freshwater algae) dominate the palynofl ora, while terrestrial species are represented by trilete spores (mainly Anemiaceae) and gymnosperm pollen grains. In the Don Bartolo Member, Classopollis spp. dominate most of the assemblages, trilete Anemiaceae spores constitute half of the total counts in one of the assemblages and a unique angiosperm species (Tricolpites variabilis) was found in two assemblages. Ephedra-type pollen grains (three genera and six species) appear in both members, although in low abundance. The results support previous sedimentology studies that indicate a perennial lake environment at the time of deposition of the Brealito Member, with evidence for dry seasonality in the Don Bartolo Member. The inferred regional paleoclimate is subtropical with arid conditions. Considering the stratigraphic ranges of selected species and the sedimentology data, an Albian/Cenomanian age is suggested for the unit.